An iterative automatic final alignment method in the ontology matching system - Gulić, Marko; Vrdoljak, Boris; Vuković, Marin (2018)
Ontology matching plays an important role in the integration of heterogeneous data sources that are described by ontologies. In order to determine correspondences between ontologies, a set of matchers can be used. After the execution of these matchers and the aggregation of the results obtained by these matchers, a final alignment method is executed in order to select appropriate correspondences between entities of compared ontologies. The final alignment method is an important part of the ontology matching process because it directly determines the output result of this process. In this paper we improve our iterative final alignment method by introducing an automatic adjustment of final alignment threshold as well as a new rule for determining false correspondences with similarity values greater than adjusted threshold. An evaluation of the method is performed on the test ontologies of the OAEI evaluation contest and a comparison with other final alignment methods is given.
Bibliografija: 27 jed.
Abstract.
Keywords: Ontologija -- Sustav automatskog podudaranja -- Heterogena integracija podataka